Transforming Self-Efficacy into High Performance: The Critical Role of McClelland’s Achievement Motivation in Labor-Intensive Work Environments - ridho, Ainur; Afifah, Zainiyatul (Eco-Entrepreneur, 2025)
Self-efficacy has long been recognized as a critical factor influencing employee performance; however, empirical evidence indicates that its impact is often indirect, requiring the role of mediating variables. This study aims to examine the effect of self-efficacy on employee performance through McClelland’s achievement motivation as a mediating variable in PT. Buana Tengka Garment. Employing a quantitative survey method, data were collected from 92 respondents selected using Slovin’s formula from a population of 120 employees. Regression analysis and Sobel test results reveal that self-efficacy does not directly affect performance but significantly influences achievement motivation, which in turn significantly impacts performance. Furthermore, achievement motivation is found to significantly mediate the relationship between self-efficacy and performance. These findings imply that improving employees’ self-efficacy must be accompanied by strategies to strengthen achievement motivation, such as setting challenging targets, implementing performance-based rewards, and providing constructive feedback, to optimize performance in labor-intensive industries